Fireless cooking - Halm, Helen; McConnel, Fay (My University, 1908)
Introduction: The principle of fireless cooking is that of recaloration, or the retention of heat previously generated, through complete insulation. It should, perhaps, be explained here that the word “fireless” is a misnomer. The proper word is “recalorator”, which literally means the conserving of heat, just as a “refrigerator” means the conserving of cold.
Citation: Halm, Helen and McConnel, Fay. Fireless cooking. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Cooking; Domestic Science; Home Economics; Heat; Graduating theses; Senior theses; Theses